Composition Systematics in the Exoskeleton of the American Lobster, Homarus americanus and Implications for Malacostraca - Mergelsberg, Sebastian T.; Ulrich, Robert N.; Xiao, Shuhai; Dove, Patricia M. (Frontiers in Earth Science, 2019)
Studies of biominerals from the exoskeletons of lobsters and other crustaceans report chemical heterogeneities across disparate body parts that have prevented the development of composition-based environmental proxy models. Anecdotal evidence, however, suggests underlying composition systematics may exist in the mineral component of this biocomposite material. We test this idea by designing a protocol to separately extract the mineral (amorphous calcium carbonate plus calcite) and organic (chitin plus protein) fractions of the exoskeleton. The fractions were analyzed by ICP-OES and other wet chemistry methods to quantify Mg, Ca, and P contents of the bulk, mineral, and organic matrix. Applying this approach to the exoskeleton for seven body parts of the American lobster, Homarus americanus, we characterize the chemical composition of each fraction. The measurements confirm Mg, P, and Ca concentrations in lobster exoskeletons are highly variable. However, the ratios of Mg/Ca and P/Ca in the mineral fraction are constant for all parts, except the chelae (claws), which are offset to higher values. By normalizing concentrations to obtain P/Ca and Mg/Ca, we show that all body parts conserve P/Mg to 1.27±0.30. The findings suggest lobsters hold promise as a novel class of animals that record composition systematics within their CaCO3 biominerals. Parallel structural analyses of the bulk samples confirm a large proportion of amorphous calcium carbonate relative to calcite in the mineral fractions for each body part using high-energy X-ray diffraction and PDF analysis. There is no evidence for a phosphate phase. Returning to compositions reported for other marine (crab, lobster, and marine shrimp) and terrestrial (pillbug) crustaceans, we find evidence for similar Mg/Ca and P/Ca patterns in these organisms. The relationships provide a basis for developing new proxies for environmental reconstructions using animals from the class Malacostraca and provide insights into how composition may be optimized to meet functional requirements of the mineral fraction in exoskeletons. Compositional variability, and hence differential solubility, suggests a thermodynamic basis for the taphonomic bias that is observed in the fossil record.